Claude Lévi-Strauss e suas relações com a obra de Sigmund Freud - Maia, Josué Felipe Silva (2016)
This research integrates the investigations with regard to the Anthropological Theory and seeks to identify convergences, divergences, incorporations and congenerous relations between two knowledges which are Structural Anthropology and the Psychoanalysis. To that, we took as empiric object the work of the french anthropologist Claude Lévi-Strauss, exponent of the structuralism in Anthropology and we elected, by cutting off, his critics and parallels presented in some of his texts in relation to Sigmund's Freud work. The chapters were conducted by discussions such as the notion of unconsciousness, interdisciplinarity among the theories, incest's interdiction and consciousness' autonomy.